66. Results of a spectrometric analysis performed at the ASST Lariana on 223Ra-dichloruro Xofigo. (December 2018) - Ostinelli, A.; Duchini, M.; Frigerio, M.; Lattuada, P.; Cacciatori, M.
Abstract : Purpose: BAYER has recently marketed a pharmaceutical named Xofigo, consisting of 223Ra-dichloride, for the treatment of metastatic bone lesions of castration-resistant prostate cancer. Its production modality consists of the neutron irradiation of a 226Ra target yielding 227Ac which, through intermediate steps, decays into 223Ra. In view of the possible presence of radionuclide impurities that may demand strong radiation protection requirements (e.g. 227Ac and 226Ra), a radiometric analysis of Xofigo was performed to rule out any contamination by other long-lived radioisotopes[1] . Methods: The spectrometry system consisted of the GEM-20 P EG&G ORTEC Hyperpure Germanium detector, the ORTEC TRIUMP-PCI-8 k multichannel analyzer, the ORTEC GammaVision spectral analysis program, and two certified calibration point sources (152Eu and 241Am). A 0.2 ml volume of radiopharmaceutical (about 200 kBq activity) was inserted into a conical test tube and the gamma emission spectrum was acquired. The detection efficiency was calculated by a dedicated application (ORTEC ANGLE v.3.0), integrated with the GammaVision software. The spectral analysis was performed by means of a specific library, containing both expected and suspected radioisotopes. Results: The spectral acquisitions (see Figure) and the related analysis (see Table) were repeated to test the reproducibility of the results and provided the following outcomes: the calculated 223Ra activity was (196 ± 9) kBq, in agreement with the one measured at sampling, and the 211Bi and 219Rn activities were absolutely compatible with the transient equilibrium condition with the 223Ra father. No radionuclides other than those expected were found above the minimum detectable activity (MDA). Conclusions: Any significant presence of radioisotope contamination in the radiopharmaceutical sample and, consequently, of issues related to long-lived radionuclides, can be excluded, ensuring both the operator and the patient protection and the safe management of the radioactive waste.